Investigating the Catalytic Properties of Active Metals Under and On the Chiral "29" Oxide via Model Studies - Schilling, Alex. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Chemistry.; Advisor: Charles Sykes.; Committee: Arthur Utz, Samuel Thomas, and Phillip Christopher.; Keywords: Chemistry, and Physical chemistry.; Heterogenous catalysis is one of the most vital classes of catalysts with applications ranging from the three-way catalytic converter found in vehicles to the mass production of pharmaceuticals to ammonia synthesis on an industrial scale. This class of catalysts is prevalent in industrial applications because it removes the need for the separation of product and catalyst and offers superior thermal stability compared to homogenous catalysts. Most industrial reactions use expensive precious metals as the active catalyst. While the reactions take place on nanoparticles of these precious metals, the emerging field of single site heterogenous catalysis (SSHC) aims to achieve 100% efficiency by reducing the size of nanoparticles to their smallest limit of a single metal atom, thus exposing all the active metal. SSHC utilizes a support which can anchor a metal atom on a surface to perform a reaction while limiting the amount of metal needed to have the reaction proceed. However, much about how these systems function on a molecular level is unknown. The work presented in this thesis aims to answer the fundamental questions of single site heterogeneous catalysis through careful study of a model system. The system we study combines a highly characterized, chiral '29' oxide support with a combination of Pt under the oxide layer and Rh over the oxide layer for H2 dissociation and CO oxidation, respectively. Careful analysis with scanning tunneling microscopy (STM), temperature programmed desorption (TPD), x-ray photoelectron spectroscopy (XPS), reflection absorption infrared spectroscopy (RAIRS), and low-energy electron diffraction (LEED) have allowed for an in-depth view of the elementary steps of these reactions at the atomic level. The oxide layer itself is unique in that it is a chiral oxide because the unit cell vectors do not align with the underlying high symmetry directions. We have discovered that by controlling the step size and direction of a Cu(111) crystal we can control the directional growth of the oxide overlayer. This overlayer acts as a long-range chiral template and can cover the entirety of the surface with a single chirality of oxide effectively amplifying the intrinsic chirality of the metal surface which exists only at step kinks. This mechanism of chiral amplification could prove invaluable to pharmaceutical heterogeneous catalysis. However, the oxide alone is not capable of catalyzing the industrial reactions presented in this thesis. By adding small amounts of catalytically active precious metals such as Pt and Rh, this oxide can also be used as a viable support from which we can draw conclusions about industrially relevant reactions on a molecular level. The reactions studied in this work are vital for both, understanding the role of interface sites and support reduction in industrial catalysts, and the functionality of the three-way catalyst. By oxidizing a PtCu SAA, and effectively blocking CO access to the Pt atom, we form a surface on which H2 can still find the Pt binding sites. The H2 can dissociate and reduce the oxide layer increasing the number of Pt sites available. This system demonstrates how the presence of Pt atoms under the oxide can help act as a balancing agent for reactions that require the existence of interface sites such as methanol formation. This model system was also applied to investigate the efficacy of CO oxidation over Rh clusters and single atoms on a thin film oxide support. By placing small amounts of Rh atoms on top of a pristine oxide layer we were able to determine that Rh acts as an efficient active site for CO oxidation which is part of the function of a three-way catalyst. Small clusters and single atoms of Rh form on the surface at ultra-low loadings leading to two potential pathways for CO oxidation.